Answer:
B
Step-by-step explanation:
Here, we want to choose the equation representing the time it will take if they worked together
Let the amount of tasks to be done be t
pedro will work at a rate of t/3
Camela will take t/2
So the joint rate will be
t/2 + t/3
This joint rate will be equal to 1
Thus, we have
t/2 + t/3 = 1
<em>Note: As you may have unintentionally missed to add the different answers, based on which we had to check who solved correctly between Tamara and Clyda's work. </em>
<em>But, I am actually solving the expression and you must note that whoever (between Tamara and Clyda's work) may have got the same answer or match the answer with mine, would be the one who solved correctly.</em>
Answer:
We conclude that whoever (between Tamara and Clyda's work) may have got the answer as
after dividing
by
, would be the one who solved it correctly.
Step-by-step explanation:
Considering the expression
![2x^4\:+\:7x^3\:-\:18x^2\:+\:11x\:-\:2](https://tex.z-dn.net/?f=2x%5E4%5C%3A%2B%5C%3A7x%5E3%5C%3A-%5C%3A18x%5E2%5C%3A%2B%5C%3A11x%5C%3A-%5C%3A2)
Lets divide the expression by ![2x^2\:-\:3x\:+\:1](https://tex.z-dn.net/?f=2x%5E2%5C%3A-%5C%3A3x%5C%3A%2B%5C%3A1)
Solution Steps:
![\frac{2x^4+7x^3-18x^2+11x-2}{2x^2-3x+1}](https://tex.z-dn.net/?f=%5Cfrac%7B2x%5E4%2B7x%5E3-18x%5E2%2B11x-2%7D%7B2x%5E2-3x%2B1%7D)
Factorizing
![\frac{\left(x-1\right)\left(2x-1\right)\left(x^2+5x-2\right)}{2x^2-3x+1}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Cleft%28x-1%5Cright%29%5Cleft%282x-1%5Cright%29%5Cleft%28x%5E2%2B5x-2%5Cright%29%7D%7B2x%5E2-3x%2B1%7D)
Factorizing
![2x^2-3x+1:\quad \left(2x-1\right)\left(x-1\right)](https://tex.z-dn.net/?f=2x%5E2-3x%2B1%3A%5Cquad%20%5Cleft%282x-1%5Cright%29%5Cleft%28x-1%5Cright%29)
![\frac{\left(x-1\right)\left(2x-1\right)\left(x^2+5x-2\right)}{\left(2x-1\right)\left(x-1\right)}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Cleft%28x-1%5Cright%29%5Cleft%282x-1%5Cright%29%5Cleft%28x%5E2%2B5x-2%5Cright%29%7D%7B%5Cleft%282x-1%5Cright%29%5Cleft%28x-1%5Cright%29%7D)
![\mathrm{Cancel\:}\frac{\left(x-1\right)\left(2x-1\right)\left(x^2+5x-2\right)}{\left(2x-1\right)\left(x-1\right)}:\quad x^2+5x-2](https://tex.z-dn.net/?f=%5Cmathrm%7BCancel%5C%3A%7D%5Cfrac%7B%5Cleft%28x-1%5Cright%29%5Cleft%282x-1%5Cright%29%5Cleft%28x%5E2%2B5x-2%5Cright%29%7D%7B%5Cleft%282x-1%5Cright%29%5Cleft%28x-1%5Cright%29%7D%3A%5Cquad%20x%5E2%2B5x-2)
![x^2+5x-2](https://tex.z-dn.net/?f=x%5E2%2B5x-2)
Thus,
![\frac{2x^4+7x^3-18x^2+11x-2}{2x^2-3x+1}=x^2+5x-2](https://tex.z-dn.net/?f=%5Cfrac%7B2x%5E4%2B7x%5E3-18x%5E2%2B11x-2%7D%7B2x%5E2-3x%2B1%7D%3Dx%5E2%2B5x-2)
Therefore, we conclude that whoever (between Tamara and Clyda's work) may have got the answer as
after dividing
by
, would be the one who solved it correctly.
Keywords: expression, division
Learn more about expression division from brainly.com/question/1575482
#learnwithBrainly
Answer:
i think a
Step-by-step explanation:
you said 10 i see five
Answer: X = 3t, Y =2 - t, Z =2
Step-by-step explanation: the plane
x + y + z =4has normal vector
M =<1,1,1> and the line
x = 1 + t, y = 2 − t, z = 2t has direction
v =<1, −1, 2>. So the vector
A= n × v
=<1, 1, 1> × <1, −1, 2>
=<2−(−1),1−2,−1−1>
=<3,−1,−2>